Daytime wave characteristics in the mesosphere lower thermosphere region: Results from the Balloon‐borne Investigations of Regional‐atmospheric Dynamics experiment. Issue 3 (24th March 2014) - Pallamraju, Duggirala; Baumgardner, Jeffrey; Singh, Ravindra P.; Laskar, Fazlul I.; Mendillo, Christopher; Cook, Timothy; Lockwood, Sean; Narayanan, R.; Pant, Tarun K.; Chakrabarti, Supriya
Abstract Results obtained from a joint INDO‐US experiment on the investigations of mesosphere/lower thermosphere wave dynamics using balloon‐borne optical dayglow measurements in combination with ground‐based optical, radio, and magnetometer data are presented. Ultraviolet OI 297.2 nm dayglow emissions that originate at 120 km were measured from low‐magnetic latitudes from onboard a balloon on 8 March 2010. This paper describes the details of a new spectrograph that is capable of making high spectral resolution (0.2 nm at 297.2 nm) and large (80°) field of view ultraviolet dayglow emission measurements and presents the first results obtained from its operation onboard a high‐altitude balloon. Waves of scale sizes ranging from 40 to 80 km in the zonal direction were observed in OI 297.2 nm emissions. Meridional scale sizes of similar waves were found to be 200 km as observed in the OI 557.7 nm emissions that originate from 100 km. Periodicities were also derived from the variations of equatorial electrojet strength and ionospheric height on that day. Common periodicities of waves (in optical, magnetic, and radio measurements) were in the range of 16 to 30 min, which result in intrinsic horizontal wave speeds in the range of 21 to 77 m s−1. It is argued that gravity waves of such scale sizes and speeds at these heights are capable of propagating well into the thermosphere because the background wind directions were favorable. These waves were potentially capable of forming the seeds for the generation of equatorial plasma irregularities which did occur on that night.